UPAYA ARAB SAUDI TERHADAP ORGANISASI KERJA SAMA ISLAM DALAM MENYELESAIKAN KONFLIK IRAN DAN ARAB SAUDI TAHUN 2013-2018 - Emil Hikmawan; Gustri Eni Putri (Dauliyah Journal of Islamic and International Affairs, 2018)
Middle East region can be realized as region which is susceptible with conflict. The conflict in Middle East which is increasingly needed constructive and sustainable effort in order to reduce a conflict potential. The problem that concern of international community is conflict involving Iran and Saudi Arabia after death penalty to Syekh Nimr Al-Nimr by Saudi Arabia government. Firstly, conflict that happened between Saudi Arabia and Iran caused by sectarianism dimension that’s mean Sunni and Shi’ah rivalry in Middle East. Then, sectarianism dimension can evolve into geopolitical competition that Saudi Arabia and Iran’s implication in Syria, Iraq and Yemen conflict. Therefore, Middle East conflict requires a peace settlement. Furthermore, the author who takes as Saudi Arabia government in order to solve Saudi Arabia and Iran conflict more likely using Islamic Cooperation Organization (OIC) involvement. Moreover, the author argue that OIC can be conflict resolution agent and Saudi Arabia has affected an OIC. On one hand, the Saudi Arabia was influencing an OIC as the largest country that invest a fund and his domination in OIC structure itself. Therefore, through his influence, Saudi Arabia more profited than military approach. On the other hand, Saudi Arabia has also utilized an OIC as instrument to gain its national interest such as to repress Iran’s influence in Middle East